2018
DOI: 10.1002/cncr.31272
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint inhibitors in triple‐negative breast cancer (TNBC): Where to go from here

Abstract: Advances in cancer immunotherapy and a growing body of research have focused on the role of the antitumor response in breast cancer. Triple-negative breast cancer (TNBC) is the most immunogenic breast cancer subtype, and there is strong evidence that tumor-infiltrating lymphocytes in TNBC have prognostic value and are associated with clinical outcome and improved survival. Evading antitumor immunity is a hallmark for the development and progression of cancer. Immunotherapy studies have focused on the role of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
125
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(134 citation statements)
references
References 77 publications
1
125
0
Order By: Relevance
“…Checkpoint inhibitors have demonstrated to prolong survival in melanoma, lung cancer and recently in PD-L1 positive metastatic TNBC [9,10]. Several programmed cell death protein 1 (PD-1) and programmed cell death ligand 1 (PD-L1) inhibitors are currently investigated in early stage and metastatic BC [11]. Phase I studies showed an increased clinical response and suggested a correlation with PD-L1 expression [12].…”
Section: Introductionmentioning
confidence: 99%
“…Checkpoint inhibitors have demonstrated to prolong survival in melanoma, lung cancer and recently in PD-L1 positive metastatic TNBC [9,10]. Several programmed cell death protein 1 (PD-1) and programmed cell death ligand 1 (PD-L1) inhibitors are currently investigated in early stage and metastatic BC [11]. Phase I studies showed an increased clinical response and suggested a correlation with PD-L1 expression [12].…”
Section: Introductionmentioning
confidence: 99%
“…Whether similar results may be achieved with chemotherapy plus immunotherapy in later lines is unknown at this time. Of note, increased ORR have been observed in patients with previously untreated metastatic TNBC with monotherapy PD-1/PD-L1 inhibitors, suggesting that these agents may be more active in less heavily pretreated metastatic disease (120).…”
Section: Immune Subtypes Of Tnbcmentioning
confidence: 99%
“…12,13 ). However, even among such potentially immunogenic cancers, immune checkpoint inhibitors benefit only a relatively small number of patients 7,12,1418 .…”
Section: Introductionmentioning
confidence: 99%